Peran Kualitas Pelayanan Rumah Sakit di Era JKN dan Masa Pandemi COVID-19 - Aqlya Zuhra Ilma; Catur Sugiarto (Universitas Kristen Indonesia Toraja, 2022)
The Covid-19 pandemic and the hospital class transition caused a decrease in the number of outpatient visitors at the Pandan Arang Hospital, Boyolali, except for the Gastroentero Hepatology (GEH) clinic. This study aims to determine the service quality by management to create patient satisfaction and loyalty, especially at the GEH clinic. In this study, the factors of service quality, customer experience, and customer perceived value that link trust and customer satisfaction to customers loyalty to find out motivate consumers or patients in the selection of hospitals. The methodology in this research is a mixed-method approach to Sequential Exploratory design, starting with interviews with the management and consultant doctors of GEH, followed by distributing questionnaires to GEH clinic patients with a total of 307 respondents at different and sequential times. The results of the study are Pandan Arang Hospital prepared infrastructure and competent human resources according to type B hospital qualifications. During the pandemic era, Pandan Arang Hospital provided outpatient services according to the recommendations of WHO and the Ministry of Health with a separate service flow between Covid-19 and Non-Covid-19 patients. The results of quantitative research found a positive and significant relationship between service quality, customer experience, customer perceived value on trust; a positive and significant relationship between service quality, customer perceived value, and trust in customer satisfaction; the positive and significant relationship between customer satisfaction and customer loyalty.